The The Readiness Evaluation of Being Legal Entity State University in terms of Asset Optimalization (A Lesson from Universitas Negeri Surabaya) - Nuri Susilawati; Tri Diana Sari; Teguh Wahyudi; Masita Nur Hayati (Cita konsultindo, 2024)
Asset management is an important factor in the process of being financially independence. Physical infrastructure is needed to create income both from academics as well as non-academics activities. Using unstructured qualitative research, this study collect data from university financial report to describe how effective is the university in using its assets. The results successfully disclose that the use of assets has already create income beyond targeted. Even though some years seems not achieved due to pandemic. This implies that the university at its best effort to optimize its assets. Based on in-depth interview, it is discovered that the assets is well-managed in terms of administrative works, but there is an ample room to improve that is integrating important issues for stakeholders into asset strategic plan. Thus all assets used may not only use at optimum capacity but also creating value for stakeholders. The idea of green business and digital business may help management to create competitive advantage. In general, UNESA is ready to change its status from Public Service Agencies into Legal Entity State University. But, to be sustain in long term, UNESA need to consider stakeholder perspectives into its strategic plan.